(3cJGH ajg MOjK MeGeI GdPgH heGLQi dgG eY bQbjShf GHfI edc MQGf ef GdYLGFH Ydi GdJeGe hGdceGds
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf Qhi Yf CejQ GdeDefjf Ydj Hf CHj WGdH Cfg bGd CJjJ Edi eSLO QShd Gddg Udi Gddg Ydjg hSde hEPG cYH GdCMHGQ LGdS jMOK s
(3BNQgG (B:s
(3Ke EfgeG ScfG aj YjTI hSQhQ hLeY GdTed HjfgeG hgPG eG GfJgi ef MOjKge Ydi GdJeGe hGdceGd s
(3Vef eLehY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B343 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JGQjN (B1779) s
Keywords: (3GdJGQjNs